Prejudice: The Role of the Media in the Development of Social Bias. (December 2013) - Bissell, Kim; Parrott, Scott
Numerous studies document the existence of bias: bias against gender, race, sexual orientation, age, mental illness, and body shape or weight. This article presents a model of bias development, which helps explain the influence of mediated, individual, social, and ideological influences on the development of bias. This article applies the proposed model using four experimental studies that examine weight bias in children and adults. The results from the four studies lend empirical support for the model. Data from the studies suggest the explication of a theoretical model is necessary to understand the factors related to the development of bias against a variety of groups, character traits, or attributes in others. It is difficult to argue that any one factor whether it be media, individual, social, or ideology "trumps" other factors as the development of bias seems to be very individualistic. Therefore, a model that represents the myriad of factors identified above is proposed.